Knockdown of CNN3 Impairs Myoblast Proliferation, Differentiation, and Protein Synthesis via the mTOR Pathway - She, Yanling; Li, Cheng; Jiang, Ting; Lei, Si; Zhou, Shanyao; Shi, Huacai; Chen, Rui (Frontiers in Physiology, 2021)
Background: Myogenesis is a complex process that requires optimal outside–in substrate–cell signaling. Calponin 3 (CNN3) plays an important role in regulating myogenic differentiation and muscle regeneration; however, the precise function of CNN3 in myogenesis regulation remains poorly understood. Here, we investigated the role of CNN3 in a knockdown model in the mouse muscle cell line C2C12. Methods: Myoblast proliferation, migration, differentiation, fusion, and protein synthesis were examined in CNN3 knockdown C2C12 mouse muscle cells. Involvement of the mTOR pathway in CNN3 signaling was explored by treating cells with the mTOR activator MHY1485. The regulatory mechanisms of CNN3 in myogenesis were further examined by RNA sequencing and subsequent gene ontology (GO) and pathway analyses. Results: During proliferation, CNN3 knockdown caused a decrease in cell proliferation and migration. During differentiation, CNN3 knockdown inhibited myogenic differentiation, fusion, and protein synthesis in C2C12 cells via the AKT/mTOR and AMPK/mTOR pathways; this effect was reversed by MHY1485 treatment. Finally, GO and gene set enrichment analysis indicated that the NOD-like receptor signaling pathway is affected in CNN3 knockdown cell lines. Conclusions: CNN3 may promote C2C12 cell growth by regulating AKT/mTOR and AMPK/mTOR signaling. The GO and gene set enrichment analyses indicated that inhibiting CNN3 may activate several pathways, including the NOD-like receptor pathway and pathways involved in necroptosis, apoptosis, and inflammation.